Queer Bodies as Im/Mobile Infrastructure: A Textual Reading of Two Pandemic Stories in the Provincial Context - Marfy M. Cabayao (Philippine Social Science Journal)
This paper examines the "queer body" as an im/mobile infrastructure, constantly navigating a heteronormative society that historically denies queer individuals a sense of belonging. Extending the concepts of mobility as capability and the body as infrastructure, the study analyzes the embodied movement and interaction of queer bodies. Through queer textual analysis of personal pandemic narratives from two Negrense queers in the Philippines, it reveals how these bodies maintain social, spatial, and existential mobility despite lockdowns. The narrators' experiences illustrate how queer bodies, as im/mobile infrastructures, utilize inner capabilities like emotions, concepts, and imaginations to navigate life spaces. These spaces offer queer bodies mobility to engage with others, spaces, and places, enabling them to live authentically with themselves and others.